Information on Genghis Khan, Berke, and Khan Uzbek in Bibliographic Collection of al-Safadi, Salah al-Din Khalil (d. 764 AH). Al-Wafi bi al-vafiyat (الوافي بالوفياب أو تاريخ الصفدي) (Complete collection of biographies of deceased persons or the history of al-Safadi) » - D.R. Zaynuddinov (Золотоордынское обозрение)
Publication of Russian translations by V.G. Tiesenhausen of extracts from Arabic sources on the history of the Golden Horde was a breakthrough in this research topic. Thanks to the work of V.G. Tiesenhausen, Russian historical school has become one of the leading research schools and remains such to the present day. However, the work of V.G. Tiesenhausen does not exhaust the entire storehouse of medieval historical and geographical literature in the Arabic language, as he states in the preface to his work. Proof of this is the fact that in voluminous work of V.G. Tiesenhausen we practically do not meet materials from the writings of historians dealing with the narrative biographies, although their works contain very valuable information about the history of the Golden Horde. As examples of such works, we can name the following: 1) al-Safadi (696 AH / 1297 – 764 AH / 1363), “Al-Wafi bi al-vafiyat” (الوافي بالوفياب أو تاريخ الصفدي) (Complete Collection of Biographies of Deceased Persons or the History of al-Safadi); 2) al-Safadi (696 AH / 1297 – 764 AH / 1363), (أعيان العصر وأعوان النصر) (Outstanding Personalities of this century, and the Champions of Victory); 3) al-Kutubi Muhamamd Shakir (d. 764 AH), (فوات الوفيات و الذيل عليها) (Biographies of Deceased Persons not included (in the collection of Ibn Hallikan (608 AH / 1211 – 681 AH / 1282)), and addition to them); 4) (al-Maqrisi Taqi al-Din) (d. 845 AH), (كتاب المقفّى الكبير) (Great Rhymed Book); 5) al-Asqalani Ibn Najar (d. 852 AH) (الدرر الكامنة في أعيان المائة الثامنة) (Hidden Pearls in a Biography of Outstanding Persons of the eighth century of Hijra); 6) Ibn Taghribirdi (813–874 AH) (المنهل الصافي المستوفي بعد الوافي) (Pure Completing Source after the “Full”). The purpose of this article is an introduction into academic circulation of the materials from biographical dictionary “Complete Collection of Biographies of Deceased Persons” written by Mamluk historian al-Safadi (696 AH / 1297 – 764 AH / 1363). This article contains: I) a brief examination of the life and creative activities of the historian and description of his works; II) description of biographical collection “Al-Wafi bi al-vafiyat” (الوافي بالوفياب أو تاريخ الصفدي) (Complete Collection of Biographies of Deceased Persons or the History of al-Safadi); III) translation and facsimiles of biographies of such khans as Genghis Khan, khan Berke, and khan Uzbek.